PENERAPAN MODEL MEMORIZATION BERBASIS GAMES DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN IPS - Tetep, Tetep; Dahlena, Alni (Sosial Khatulistiwa: Jurnal Pendidikan IPS, 2023)
The low interest of students in social studies subjects is possible because the teacher's efforts have not been optimal to increase the creative thinking of students' learning. Students' critical thinking skills are still low, seen during the current learning process, students are not encouraged to improve their thinking skills. The purpose of this study was to identify an increase in students' critical thinking skills after applying the games-based learning model of memorization. This study uses a quantitative method, this type of research uses a quasy experiment, the sample in this study is class VII students at SMPN 1 Tarogong Kidul, the instruments used for critical thinking skills are pretest and posttest, observation and documentation study. Based on the results of research and data management using the Mann Whitney test, the value of Sig.0.021 and α = 0.05 means Sig. < α, then the game-based memorization learning model can improve students' critical thinking skills. So that students have the skills and abilities to think critically in the social studies learning process.Keywords: Memorization Model, Critical Thinking Ability, Social Studies Learning.